Government Finance Statistics Yearbook, 2006. (Government Finance Statistics; Government Finance Statistics ;, 2006)
Detailed annual data for Fund member governments are supplied on revenue income by source (tax, lending, bonds, et cetera), and expenditure by sector (defense, education, health, et cetera) for all levels of government (national, state, local). Topics covered include deficit/surplus or total financing, revenues or grants, expenditures, lending minus repayments, domestic financing, foreign financing, domestic debt or total debt, and foreign debt. The Yearbook provides data on budgetary operations, extra-budgetary operations, social security, and consolidated financial operations of central governments. A section of the Government Finance Statistics Yearbook is devoted to a cross-country comparison of data.